2023
DOI: 10.3390/biomimetics8060481
|View full text |Cite
|
Sign up to set email alerts
|

A Path-Planning Method Based on Improved Soft Actor-Critic Algorithm for Mobile Robots

Tinglong Zhao,
Ming Wang,
Qianchuan Zhao
et al.

Abstract: The path planning problem has gained more attention due to the gradual popularization of mobile robots. The utilization of reinforcement learning techniques facilitates the ability of mobile robots to successfully navigate through an environment containing obstacles and effectively plan their path. This is achieved by the robots’ interaction with the environment, even in situations when the environment is unfamiliar. Consequently, we provide a refined deep reinforcement learning algorithm that builds upon the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The number of input layers and the quantitative relationship is G = T + 1. The input vector is shown in equation (18). The second layer of the RBF network is the hidden layer with s nodes and the basis function is j k (Y) (k = 1, 2, L, T, G).…”
Section: Q-table Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of input layers and the quantitative relationship is G = T + 1. The input vector is shown in equation (18). The second layer of the RBF network is the hidden layer with s nodes and the basis function is j k (Y) (k = 1, 2, L, T, G).…”
Section: Q-table Improvementmentioning
confidence: 99%
“…Taking the CJ8 environment as an example, when the mobile robot traveled to the coordinate points of (5, 25), (7,15), (18,14), and (24, 10), it was observed that there was a dynamic obstacle in the vicinity that changed its state, and according to this paper's algorithm, it changed the direction of the mobile robot's operation in advance, chose the next action and coordinates, and then changed the traveling route to successfully avoid obstacles and continue the path planning. It is proved that the practicality of this paper's algorithm is good.…”
Section: Path Planning Experiments In Dynamic Environmentmentioning
confidence: 99%
See 1 more Smart Citation